2007
DOI: 10.1142/s021827180701047x
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Properties of Galaxy Morphological Types in Compact Groups of Main Galaxies From the SDSS Data Release 4

Abstract: In order to explore the statistical properties of galaxy morphological types in compact groups (CGs), we construct a random group sample which has the same distributions of redshift and number of member galaxies as those of the CG sample. It turns out that the proportion of early-type galaxies in different redshift bins for the CG sample is statistically higher than that for random group sample, and with growing redshift z this kind of difference becomes more significant. This may be due to the existence of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…This shows that the luminosity is not strongly correlated with environment. A similar conclusion was obtained by Deng et al (2007). They compared statistical properties of galaxy luminosity in a compact galaxy group sample with those in a random group sample, and found that the two samples had the same statistical properties of luminosity.…”
Section: Correlations Between Galaxy Properties and Environmentsupporting
confidence: 75%
See 2 more Smart Citations
“…This shows that the luminosity is not strongly correlated with environment. A similar conclusion was obtained by Deng et al (2007). They compared statistical properties of galaxy luminosity in a compact galaxy group sample with those in a random group sample, and found that the two samples had the same statistical properties of luminosity.…”
Section: Correlations Between Galaxy Properties and Environmentsupporting
confidence: 75%
“…clusters or groups) have a high proportion of early type morphologies (e.g. Oemler 1974;Dressler 1980;Whitmore et al 1993;Deng et al 2007) and low SFRs (e.g. Balogh et al 1997Poggianti et al 1999).…”
Section: Correlations Between Galaxy Properties and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that galaxy morphologies strongly depend on local environment: galaxies in dense environments (i.e., clusters or groups) have a higher proportion of early-type morphologies [1][2][3][4], while galaxies in the lowest density regions (isolated galaxies) have a lower proportion of early-type galaxies [55]. Deng et al [43] also found that galaxy morphologies strongly depend on local environment.…”
Section: Correlations Between Galaxy Properties and Local Galaxy Densitymentioning
confidence: 99%
“…Numerous studies have shown that galaxy properties seem to correlate (significantly) with environment, for example, galaxies in dense environments (i.e., clusters or groups) have a higher proportion of early type morphologies [1][2][3][4] and low SFRs [5][6][7]. Many authors have investigated the correlations between environment and galaxy properties, such as those between environment and morphology [8][9][10][11][12][13][14][15][16][17], those between environment and star formation rate [18][19][20][21][22][23][24], and those between environment and color [17,23,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%